The synchrony effect revisited: chronotype, time of day and cognitive performance in a semantic analogy task - Nowack, Kati; Van Der Meer, Elke (Chronobiology international, 2018)
The synchrony effect (i.e. superior performance at optimal, inferior performance at suboptimal times of day) has been broadly studied within the context of circadian rhythms. Whether one chronotype copes better with the synchrony effect than the other received only insufficient empirical attention. We report on an applied experimental study investigating the impact of chronotype on the synchrony effect in a semantic analogy task. To detect an analogy, 36 participants (12 males) aged between 18 and 40 had to decide whether the relation between events of a source pair was mirrored by the relation between events of a target pair (e.g. to cook: to eat = to saddle: to ride). Temporal orientation of the relation within each event pair was varied corresponding either to the chronological or reverse order. Response times (RTs), error rates, as well as the psychophysiological parameters pre-experimental pupil baseline and peak pupil dilation replicate findings of a synchrony effect (shorter RTs and allocation of less cognitive resources at optimal times of day) and show an impact of chronotype (morning types generally outperforming evening types). Most importantly, morning types appeared to cope better with the synchrony effect than evening types: At suboptimal times, morning types solved the analogy detection task more efficient; that is faster with the same accuracy and without the investment of more cognitive resources. They also showed greater alertness and wakefulness indexed by greater pre-experimental pupil baselines. At optimal times of day, morning types have more cognitive resources available to allocate these to the more demanding conditions to outperform evening types. We interpret these findings to suggest that morning types are more able to adapt to unfavourable circumstances (for instance, by avoiding wasteful resource allocation when there are less cognitive resources available). Evening types appear less able to adapt to suboptimal times than morning types, because they have to deal with social jetlag and decreased self-control.